Relationship Between Cognitive Linguistic Abilities And Syntaxic Abilities Of Early Childhood In Surakarta - Aqilah, Risma Narda; Muryanti, Muryanti; Susanti, Nadya (Jurnal EduHealth, 2025)
Early childhood is a golden period of physical, emotional, social and intellectual growth and development. During this period, optimal stimulation is required so that children's potential can develop and flourish to the full. Early childhood development focuses on cognitive and physical-motor aspects.  Cognitive linguistics is concerned with how humans think when they speak, and how they speak when they think about something.  Syntaxic studies the organization and relationship between words and words, or between words and larger units, or between larger units in language. Syntaxic ability is problematic because linguistic cognitive ability is problematic. Indeed, syntaxic and cognitive linguistic ability are linked to the way human beings process language. The impact of a syntaxic ability problem is the construction of incoherent, ungrammatical and inefficient sentences. The aim of this study is to determine the relationship between linguistic cognitive ability and syntaxic ability.  This research method is cross sectional study. The sample for this study consisted of 59 early childhood.  Data analysis was carried out using the Spearman Rank method.  The results of the analysis obtained a significant value (p-value) of 0.000. The significant value of the test is less than 0.05 (0.000 < 0.05), which means that there is a significant relationship between linguistic cognitive ability and syntaxic ability of early childhood in Surakarta